2014
DOI: 10.1002/pd.4374
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response and time-response analysis of total fatty acid ethyl esters in meconium as a biomarker of prenatal alcohol exposure

Abstract: Light-to-moderate prenatal alcohol exposure cannot be reliably predicted by the cumulative FAEE concentrations in meconium of exposed babies. A cumulative FAEE level of >10 nmol/g would be required to consider that prenatal alcohol exposure during the second to third trimesters occurred at risky levels in the absence of reliable maternal history of ethanol exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(33 reference statements)
2
13
0
1
Order By: Relevance
“…The detection has been focused in the use of questionnaires about alcohol consumption and biomarkers of exposure [6]. Up to date, the determination of fatty acid ethyl esters (FAEEs) or ethyl glucuronide (EtG) in meconium or maternal hair is the best procedure to identify exposed newborns, but with a cut off value in the range of heavy drinking population [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The detection has been focused in the use of questionnaires about alcohol consumption and biomarkers of exposure [6]. Up to date, the determination of fatty acid ethyl esters (FAEEs) or ethyl glucuronide (EtG) in meconium or maternal hair is the best procedure to identify exposed newborns, but with a cut off value in the range of heavy drinking population [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriately sensitive and specific maternal biomarkers for recent alcohol consumption are being developed. At birth, it is possible to detect some patterns of prenatal alcohol exposure by infant biomarkers (Bakhireva et al., ; Kwak et al., ). It is also possible to identify children with physical features of FASD in the newborn period through a targeted dysmorphology examination (Jones and Smith, ).…”
mentioning
confidence: 99%
“…In contrast, a growing number of epidemiological studies have consistently found a lack of short- and long-term adverse maternal and fetal outcomes when exposure occurred at low or very low levels ( Kelly et al 2013 , Han et al 2012 , O’Leary et al 2013 , Robinson et al 2010 ). Aligned with these findings, our group recently reported a study where the sum of nine different FAEEs was found to be an unreliable composed biomarker of low prenatal alcohol exposure ( Kwak et al 2014a ). However, the possibility that at least one of the FAEEs remained linearly correlated to the intensity of alcohol ingestion was not explored.…”
Section: Introductionmentioning
confidence: 70%